Early diagnostics and correction of ASD in the field of emotional-semantic approach - Baenskaya E.R (Moscow State University of Psychology and Education, 2017)
The content of the emotional-semantic correctional approach, which is aimed at overcoming the distortion of mental development of a child with autism, is revealed. Emotional development of a child, which exists in a shared experience with an adult, is a prerequisite for the formation of their active meaningful relationship with the world. An idea of the first significant markers of autistic development tendencies is given. The aims, the content, the techniques of correctional work with an early age autistic child and methods of assisting their relatives are shown.